(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Laree food is ready-to-eat food or drink served by a hawker or seller at a Laree or another public venue, such as a market or fair, typically from a temporary stall. While many Laree dishes have expanded outside of their original location, some are still regional in nature. In addition to being categorized as fast food and finger food, most Laree items are typically less expensive than restaurant meals. A 2007 Food and Agriculture Organization survey estimates that 2.5 billion people consume Laree food daily. These days, people buy Laree food for a variety of reasons, including nostalgia, sampling different ethnic cuisines, and getting tasty, affordable meals in a social environment.